A 'requiem' for global citizenship education in higher education? An analysis of the exclusive nationalistic response to the COVID-19 pandemic. Issue 1 (1st February 2022) - Hungwe, Joseph Pardon
Global citizenship education is premised on the narrative of an increasingly interconnected and interdependent world. However, the rise in exclusive nationalistic response to the COVID-19 has indented the central tenets of global citizenship education. In the midst of the COVID-19 pandemic, the triumphalism of exclusive nationalistic responses to COVID-19 has manifested in an increase in nationalism rhetoric, border closure, reinforcement of border fences the repatriation of foreign nationals and evacuation of citizens. In some instances, foreign nationals have been denied COVID-19 state food handouts. Consequently, there has been a rise in xenophobia, sinophobia and other forms of racial discrimination, which have affected the higher education sector. Contrastingly, global citizenship education envisions a global collective response to a phenomenon, such as the COVID-19 pandemic. This article explores and analyses the complex challenges that the COVID-19 pandemic has imposed on global citizenship education.